The Physiological and Agronomic Responses to Nitrogen Dosage in Different Sugarcane Varieties - Yang, Yingying; Gao, Shiwu; Jiang, Yong; Lin, Zhaoli; Luo, Jun; Li, Mingjie; Guo, Jinlong; Su, Yachun; Xu, Liping; Que, Youxiong (Frontiers in Plant Science, 2019)
Nitrogen (N) is very important for sugarcane yield improvement, but the excessive application of N fertilizer brings about N pollution and a cost increase. Through distinguishing the difference of nitrogen use efficiency (NUE), we can reasonably apply N fertilizer according to the NUE characteristics of sugarcane varieties, and thus reduce N loss and maintain high yield. The present study showed the pot experiment results of identifying NUE types of nine main sugarcane varieties in the main sugarcane producing areas of China under controlled conditions, and identified the key physiological and agronomic indictors which can help to determine the NUE types of sugarcane. The test clones were exposed to varying levels of N fertilizer and 15 parameters that are likely to impact NUE were measured. The key results are 1) sugarcane variety ROC22 has the high plant dry weight (PDW) and NUE among nine varieties under different N rates, it can take advantages under low N supply (225 kg/hm2 urea), and less N fertilizer can be applied properly in production. 2) Varieties of GT32 was good performing genotype for PDW and NUE under low N supply (225 kg/hm2 urea), GT42 was more suitable for moderate N environment (450 kg/hm2 urea), while YT94-128 was at middle N and high N supply (450-675 kg/hm2 urea). 3) Late stage of shoot elongation is suitable for differentiating sugarcane clones for NUE. 4) Leaf glutamine synthetase is the most reliable predictor of NUE in sugarcane. The result of pot experiment is sufficient to differentiate clonal variation for NUE in sugarcane as it reflects field experimental results. This study can set up a basis for identification the NUE types of sugarcane varieties and the development of reasonable N fertilizer application.